1993
DOI: 10.1111/j.1699-0463.1993.tb00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐gamma and resistance to bacterial infections

Abstract: Since its initial description as an antiviral, it has become clear that Interferon-y (IFN-y) has potent immunoregulatory and cell growth regulatory activities. As a result of these additional activities, it is now apparent that IFNy plays a major role in regulation of bacterial infections. IFN-y can be both induced by bacteria and bacterial products; endogenous IFN-y production has been shown to play a protective role in the natural host response to several bacterial infections; and administration of exogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 107 publications
1
5
0
Order By: Relevance
“…G. bethesdensis -stimulated normal monocytes pre-treated with IFN-γ produced significantly more superoxide, as measured by chemiluminescence, compared to monocytes not receiving IFN-γ (data not shown), suggesting a link between induced superoxide and enhanced antibacterial activity after IFN-γ treatment. These data confirm that IFN-γ treatment is important for the maintenance of in vitro monocyte bactericidal activity and may augment phagocytic killing in vivo (29, 30). …”
Section: Resultssupporting
confidence: 71%
“…G. bethesdensis -stimulated normal monocytes pre-treated with IFN-γ produced significantly more superoxide, as measured by chemiluminescence, compared to monocytes not receiving IFN-γ (data not shown), suggesting a link between induced superoxide and enhanced antibacterial activity after IFN-γ treatment. These data confirm that IFN-γ treatment is important for the maintenance of in vitro monocyte bactericidal activity and may augment phagocytic killing in vivo (29, 30). …”
Section: Resultssupporting
confidence: 71%
“…It suggested that TGF-β1 was suppressed at the initial phase of mammary infection . IFN-γ is a cytokine that is very important for innate and adaptive immunity against infection of virus and intracellular bacteria [ 23 ]. The mRNA expression of IFN-γ decreased slightly at 6 and 12 h pi, but increased dramatically at 48 h pi and then declined gradually at 72 and 96 h pi (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of meningitic infections, consideration of IFNg is often focused on its protective role, associated primarily with modulating bacterial clearance (Czarniecki and Sonnenfeld 1993;Rottenberg and others 2000;Shtrichman and Samuel 2001;Siddiqui and others 2005;Sasaki and others 2006). In our previous (Mitchell and others 2012;Too and others 2014) and present findings, however, we demonstrate that IFNg and its downstream effects may, in part, drive the pathogenesis of PM.…”
Section: Introductionmentioning
confidence: 99%